Electromagnetic compatibility analysis of projected capacitive touch technology based panel computer for military application. Issue 13 (1st September 2016) - Mathur, Manisha; Rai, J. K.; Sridhar, N.
ABSTRACT: Touch screens are gaining popularity in military display application. Projected capacitive touch screens offer feather touch experience to user apart from excellent image clarity, multitouch feature and resistance to surface contamination. The biggest limitation of capacitive screens in military application is that it is prone to electromagnetic radiations. Hence, its compliance to military standard 461F for electromagnetic compatibility is a challenge to designers. In this paper, results of various electromagnetic compatibility tests such as CE102, CS101, CS114, CS115, CS116, RE102 and RS103 are presented which are conducted as per guidelines given in military standard 461F to check the compliance and suitability for military application. Experimental test results show that the projected capacitive screens are showing problems with RS103 requirement and relaxation of 30 V/m is given to clear the tests. Another failure is that the radiated emission test RE102 overshoots beyond the limit line. Failure of RE102 suggests that projected capacitive touch screens are unsuitable for military display application unless electromagnetic compatibility issue is addressed specific to RE102 test.